Synthesis, Analysis, and Testing of BiOBr-Bi2WO6 Photocatalytic Heterojunction Semiconductors - Xiangchao Meng; Zisheng Zhang (International Journal of Photoenergy)
In photocatalysis, the recombination of electron-hole pairs is generally regarded as one of its most serious drawbacks. The synthesis of various composites with heterojunction structures has increasingly shed light on preventing this recombination. In this work, a BiOBr-Bi2WO6 photocatalytic heterojunction semiconductor was synthesized by the facile hydrothermal method and applied in the photocatalytic degradation process. It was determined that both reaction time and temperature significantly affected the crystal structure and morphologies of the photocatalysts. BiOBr (50 at%)-Bi2WO6 composites were prepared under optimum synthesis conditions (120°C for 6 h) and by theoretically analyzing the DRS results, it was determined that they possessed the suitable band gap (2.61 eV) to be stimulated by visible-light irradiation. The photocatalytic activities of the as-prepared photocatalysts were evaluated by the degradation of Rhodamine B (RhB) under visible-light irradiation. The experimental conditions, including initial concentration, pH, and catalyst dosage, were explored and the photocatalysts in this system were proven stable enough to be reused for several runs. Moreover, the interpreted mechanism of the heterojunction enhancement effect proved that the synthesis of a heterojunction structure provided an effective method to decrease the recombination rate of the electron-hole pairs, thereby improving the photocatalytic activity.